SOCIAL FACTORS PROMPTING ADULT BILINGUAL SPEAKERS TO CODE SWITCH - Yunita Reny Bani Bili (Universitas Islam Negeri Banda Aceh, 2017)
It has been long known that bilinguals can switch their speeches from one language to another when interacting within their own community. Some experts argue that code switch occurs due to the lack of proficiency in languages, lazy choices and easy solutions in communicating, and impact of linguistic dominance. This paper describes the social factors which promote adult bilinguals in code switching. The paper focuses on three types of the social factors contributing to code switching.The first type deals with factors independent of specific speakers and circumstances such as prestige, cover prestige, and power relation. The second one is related to speakers’ competence both as individuals and members of a sub group. The last category refers to factors within the conversation where code switching emerges. To conclude, these social factors are highly relevant in prompting adult bilinguals to code switch.